Study guides

Q: Factor the following expressions 3a plus 9b?

Write your answer...

Submit

Related questions

3a(2a + 1)

9a^2 + 42at + 49t^2 = (3a + 7t)(3a + 7t)

3a+ax+3b+bx = 3(a+b)+(a+b)x = (a+b)(3+x)

(x + 3)(a + b)

(3a - 4)(3a - 4)

(2a+1)(a+1)

(b + 3)(a + c)

7a minus 2, if "3a-2" means 3a minus 2. 3a plus 1 and 1-3rd in parenthesis times 3a, if "3a-2" means 3a squared. a plus 3a squared plus 3a = 1-3rd times 3a plus 3a times 3a plus 1 times 3a = 3a plus 1 and 1-3rd in parenthesis times 3a

a(a^2 - 9a + 3)

The GCF is a.

a(b+3)+b(b+3)

Yes.

3ab + 3ac + 2b2 + 2bc = 3a(b + c) + 2b(b + c) = (3a + 2b)(b + c)

3a(b+c)+2b(b+c)

(2a - 1)(3a + 4)

5(3a - 5b + 4)

a(2y - 1)(y + 3)

a(4a - 3)(3a - 5)

0

(2a - 3)(3a - 4)

It is: (2a+3)(3a+4) when factored

(3a - 2c)(b - d)

It is 6a + 4

What is the solution of -2a plus 3a plus 5b

a + 3a - 2 + 3a. Add the a + 3a + 3a = 7a. You can't combine the -2 & 7a so the solution is: 7a - 2.